Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Differential interspecific responses of symbiotic luminous bacteria Vibrio spp. in a cephalopod host to marine heatwaves - Eve Otjacques; Nicolina G. Ranieri; Tiago Repolho; José C. Xavier; Edward Ruby; Margaret McFall-Ngai; Rui Rosa (Marine Biology, 2026)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Transcriptional characterization of Vibrio fischeri during colonization of juvenile Euprymna scolopes - Luke R. Thompson; Kiel Nikolakakis; Shu Pan; Jennifer Reed; Rob Knight; Edward G. Ruby (Environmental Microbiology, 2017)
Summary The marine bacterium Vibrio fischeri is the monospecific symbiont of the Hawaiian bobtail squid, Euprymna scolopes , and the establishment of this association involves a number of signaling pathways and transcriptional responses between both partners. We report here the first full RNA‐Seq dataset representing host‐associated V. fischeri cells from colonized juvenile E. scolopes , as well as comparative transcriptomes under both laboratory and simulated marine planktonic conditions. These data elucidate the broad transcriptional changes that these bacteria undergo during the early stages of symbiotic colonization. We report several previously undescribed and unexpected transcriptional responses within the early stages of this symbiosis, including gene expression patterns consistent with biochemical stresses inside the host, and metabolic patterns distinct from those reported in associations with adult animals. Integration of these transcriptional data with a recently developed metabolic model of V. fischeri provides us with a clearer picture of the metabolic state of symbionts within the juvenile host, including their possible carbon sources. Taken together, these results expand our understanding of the early stages of the squid–vibrio symbiosis, and more generally inform the transcriptional responses underlying the activities of marine microbes during host colonization.

Non‐native acylated homoserine lactones reveal that LuxIR quorum sensing promotes symbiont stability - Sarah V. Studer; Julia A. Schwartzman; Jessica S. Ho; Grant D. Geske; Helen E. Blackwell; Edward G. Ruby (Environmental Microbiology, 2014)
Summary Quorum sensing, a group behaviour coordinated by a diffusible pheromone signal and a cognate receptor, is typical of bacteria that form symbioses with plants and animals. LuxIR ‐type N ‐acyl L‐homoserine ( AHL ) quorum sensing is common in Gram‐negative Proteobacteria , and many members of this group have additional quorum‐sensing networks. The bioluminescent symbiont V ibrio fischeri encodes two AHL signal synthases: AinS and LuxI . AinS ‐dependent quorum sensing converges with LuxI ‐dependent quorum sensing at the LuxR regulatory element. Both AinS ‐ and LuxI ‐mediated signalling are required for efficient and persistent colonization of the squid host, E uprymna scolopes . The basis of the mutualism is symbiont bioluminescence, which is regulated by both LuxI ‐ and AinS ‐dependent quorum sensing, and is essential for maintaining a colonization of the host. Here, we used chemical and genetic approaches to probe the dynamics of LuxI ‐ and AinS ‐mediated regulation of bioluminescence during symbiosis. We demonstrate that both native AHLs and non‐native AHL analogues can be used to non‐invasively and specifically modulate induction of symbiotic bioluminescence via LuxI ‐dependent quorum sensing. Our data suggest that the first day of colonization, during which symbiont bioluminescence is induced by LuxIR , is a critical period that determines the stability of the V . fischeri population once symbiosis is established.

Features governing symbiont persistence in the squid–vibrio association - Eric J. Koch; Tim Miyashiro; Margaret J. McFall‐Ngai; Edward G. Ruby (Molecular Ecology, 2014)
Experimental studies of the interaction between host and symbiont in a maturing symbiotic organ have presented a challenge for most animal–bacterial associations. Advances in the rearing of the host squid Euprymna scolopes have enabled us to explore the relationship between a defect in symbiont light production and late‐stage development ( e.g . symbiont persistence and tissue morphogenesis) by experimental colonization with specific strains of the symbiont Vibrio fischeri . During the first 4 weeks postinoculation of juvenile squid, the population of wild‐type V. fischeri increased 100‐fold; in contrast, a strain defective in light production (Δ lux ) colonized normally the first day, but exhibited an exponential decline to undetectable levels over subsequent weeks. Co‐colonization of organs by both strains affected neither the trajectory of colonization by wild type nor the decline of Δ lux levels. Uninfected animals retained the ability to be colonized for at least 2 weeks posthatch. However, once colonized by the wild‐type strain for 5 days, a subsequent experimentally induced loss of the symbionts could not be followed by a successful recolonization, indicating the host's entry into a refractory state. However, animals colonized by the Δ lux before the loss of their symbionts were receptive to recolonization. Analyses of animals colonized with either a wild‐type or a Δ lux strain revealed slight, if any, differences in the developmental regression of the ciliated light‐organ tissues that facilitate the colonization process. Thus, some other feature(s) of the Δ lux strain's defect also may be responsible for its inability to persist, and its failure to induce a refractory state in the host.

The first engagement of partners in the E uprymna scolopes – V ibrio fischeri symbiosis is a two‐step process initiated by a few environmental symbiont cells - Melissa A. Altura; Elizabeth A. C. Heath‐Heckman; Amani Gillette; Natacha Kremer; Anne‐Marie Krachler; Caitlin Brennan; Edward G. Ruby; Kim Orth; Margaret J. McFall‐Ngai (Environmental Microbiology, 2013)
Summary We studied the E uprymna scolopes – V ibrio fischeri symbiosis to characterize, in vivo and in real time, the transition between the bacterial partner's free‐living and symbiotic life styles. Previous studies using high inocula demonstrated that environmental V . fischeri cells aggregate during a 3 h period in host‐shed mucus along the light organ's superficial ciliated epithelia. Under lower inoculum conditions, similar to the levels of symbiont cells in the environment, this interaction induces haemocyte trafficking into these tissues. Here, in experiments simulating natural conditions, microscopy revealed that at 3 h following first exposure, only ∼ 5 V . fischeri cells aggregated on the organ surface. These cells associated with host cilia and induced haemocyte trafficking. Symbiont viability was essential and mutants defective in symbiosis initiation and/or production of certain surface features, including the M am7 protein, which is implicated in host cell attachment of V . cholerae , associated normally with host cilia. Studies with exopolysaccharide mutants, which are defective in aggregation, suggest a two‐step process of V . fischeri cell engagement: association with host cilia followed by aggregation, i.e. host cell–symbiont interaction with subsequent symbiont–symbiont cell interaction. Taken together, these data provide a new model of early partner engagement, a complex model of host–symbiont interaction with exquisite sensitivity.

The haem‐uptake gene cluster in Vibrio fischeri is regulated by Fur and contributes to symbiotic colonization - Alecia N. Septer; Yanling Wang; Edward G. Ruby; Eric V. Stabb; Anne K. Dunn (Environmental Microbiology, 2011)
Summary Although it is accepted that bacteria‐colonizing host tissues are commonly faced with iron‐limiting conditions and that pathogenic bacteria often utilize iron from host‐derived haem‐based compounds, the mechanisms of iron acquisition by beneficial symbiotic bacteria are less clear. The bacterium Vibrio fischeri mutualistically colonizes the light organ of the squid Euprymna scolopes . Genome sequence analysis of V. fischeri revealed a putative haem‐uptake gene cluster, and through mutant analysis we confirmed this cluster is important for haemin use by V. fischeri in culture. LacZ reporter assays demonstrated Fur‐dependent transcriptional regulation of cluster promoter activity in culture. GFP‐based reporter assays revealed that gene cluster promoter activity is induced in symbiotic V. fischeri as early as 14 h post inoculation, although colonization assays with the haem uptake mutant suggested an inability to uptake haem does not begin to limit colonization until later stages of the symbiosis. Our data indicate that the squid light organ is a low iron environment and that haem‐based sources of iron are used by symbiotic V. fischeri cells. These findings provide important additional information on the availability of iron during symbiotic colonization of E. scolopes by V. fischeri , as well as the role of haem uptake in non‐pathogenic host‐microbe interactions.

Natural transformation of Vibrio fischeri requires tfoX and tfoY - Amber Pollack‐Berti; Michael S. Wollenberg; Edward G. Ruby (Environmental Microbiology, 2010)
Summary Recent evidence has indicated that natural genetic transformation occurs in Vibrio cholerae, and that it requires both induction by chitin oligosaccharides, like chitohexaose, and expression of a putative regulatory gene designated tfoX . Using sequence and phylogenetic analyses we have found two tfoX paralogues in all sequenced genomes of the genus Vibrio . Like V. cholerae , when grown in chitohexaose, cells of V. fischeri are able to take up and incorporate exogenous DNA. Chitohexaose‐independent transformation by V. fischeri was observed when tfoX was present in multicopy. The second tfoX paralogue, designated tfoY, is also required for efficient transformation in V. fischeri , but is not functionally identical to tfoX . Natural transformation of V. fischeri facilitates rapid transfer of mutations across strains, and provides a highly useful tool for experimental genetic manipulation in this species. The presence of chitin‐induced competence in several vibrios highlights the potential for a conserved mechanism of genetic exchange across this family of environmentally important marine bacteria.

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Recognition between symbiotic Vibrio fischeri and the haemocytes of Euprymna scolopes - Spencer V. Nyholm; Jennifer J. Stewart; Edward G. Ruby; Margaret J. McFall‐Ngai (Environmental Microbiology, 2009)
Summary The light organ crypts of the squid Euprymna scolopes permit colonization exclusively by the luminous bacterium Vibrio fischeri. Because the crypt interior remains in contact with seawater, the squid must not only foster the specific symbiosis, but also continue to exclude other bacteria. Investigation of the role of the innate immune system in these processes revealed that macrophage‐like haemocytes isolated from E. scolopes recognized and phagocytosed V. fischeri less than other closely related bacterial species common to the host's environment. Interestingly, phagocytes isolated from hosts that had been cured of their symbionts bound five times more V. fischeri cells than those from uncured hosts. No such change in the ability to bind other species of bacteria was observed, suggesting that the host adapts specifically to V. fischeri . Deletion of the gene encoding OmpU, the major outer membrane protein of V. fischeri , increased binding by haemocytes from uncured animals to the level observed for haemocytes from cured animals. Co‐incubation with wild‐type V. fischeri reduced this binding, suggesting that they produce a factor that complements the mutant's defect. Analyses of the phagocytosis of bound cells by fluorescence‐activated cell sorting indicated that once binding to haemocytes had occurred, V. fischeri cells are phagocytosed as effectively as other bacteria. Thus, discrimination by this component of the squid immune system occurs at the level of haemocyte binding, and this response: (i) is modified by previous exposure to the symbiont and (ii) relies on outer membrane and/or secreted components of the symbionts. These data suggest that regulation of host haemocyte binding by the symbiont may be one of many factors that contribute to specificity in this association.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

TheVibrio fischeri sapABCDF locus is required for normal growth, both in culture and in symbiosis - Claudia Lupp; Robert E. W. Hancock; Edward G. Ruby (Archives of Microbiology, 2002)